2013
DOI: 10.1111/cid.12043
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Studies of Epithelial Cell Behavior around Titanium Implants with Machined and Rough Surfaces

Abstract: Ms implants are a better choice for integration with an epithelial wound healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…First, we investigated the OECs adhesion to Ti and Zr plates with fluorescence staining. As shown in Figure A, numerous intracellular punctate signals of adhesion proteins were observed on both plates, supporting previous findings with rat OECs on Ti plates . However, we observed slight differences in Ln‐332, In‐β4, and plectin expression between the substrates at the point of accumulation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…First, we investigated the OECs adhesion to Ti and Zr plates with fluorescence staining. As shown in Figure A, numerous intracellular punctate signals of adhesion proteins were observed on both plates, supporting previous findings with rat OECs on Ti plates . However, we observed slight differences in Ln‐332, In‐β4, and plectin expression between the substrates at the point of accumulation.…”
Section: Discussionsupporting
confidence: 91%
“…As shown in Figure 5A, numerous intracellular punctate signals of adhesion proteins were observed on both plates, supporting previous findings with rat OECs on Ti plates. 16 However, we observed slight differences in Ln-332, In-β4, and plectin expression between the substrates at the point of accumulation. In the western blotting analyses, OECs on the Zr plates also had slightly weaker expression of In-β4 or Plectin than those on the Ti plates (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, these alterations can also induce a change in the surface topography. Considering that a roughened surface has a negative effect on soft tissue cell adhesion [7,8], such alterations often lead to dental plaque accumulation on exposed implant surfaces in the oral cavity. A previous study showed that spontaneous progression of peri-implantitis was more pronounced around implants with a roughened surface compared with implants with a polished surface [9].…”
Section: Introductionmentioning
confidence: 99%